Comparison of hepatic transcriptome profiling between acute liver injury and acute liver failure induced by acetaminophen in mice. (February 2018) - Li, Chunmin; Ming, Yanan; Hong, Wenting; Tang, Yingyue; Lei, Xiaohong; Li, Xiaobo; Mao, Yimin
Highlights: Stable mouse models of acute drug-induced hepatic injury (DILI) and acute drug-induced hepatic failure (DILF) were developed. Comparison of hepatic transcriptome profiling between DILI group and DILF group by RNA sequencing analysis. Serum Btc might have potential as a biomarker for the prediction of DILI with good prognosis. Abstract: Acetaminophen (APAP) overdose is a leading cause of drug-induced acute liver failure in many countries. In the present study, we developed stable mouse models of acute drug-induced hepatic injury (DILI) and acute drug-induced hepatic failure (DILF) by sub-lethal and lethal APAP injection respectively. The differences in hepatic transcriptome profiling between these two models were compared by RNA sequencing, which were validated by qPCR, western-blot and ELISA. In results, serum IL-6, TNF-a and IL-10 levels are higher in DILF than in DILI. The upregulated genes in DILF compared with DILI were mostly enriched in the areas of "cellular development process", "cell division", "multicellular organism development, " etc. The downregulated genes in DILF compared with DILI were mostly enriched in the areas of "cellular response to chemical stimulus", "cellular response to stress", "cell activation, " etc. Sub-lethal doses of APAP increased Myc, Bag3 and Btc expression in mouse liver, but lethal doses of APAP did not, which suggested that these three genes might play important roles in adaptive protection reactions in DILI. The serum Btc level might be a potential biomarker of drug induced liver injury with good prognosis. Our data can help us better understand the mechanisms of hepatotoxicity that influence prognosis and seek novel prognostic indicators of DILI.